2016
DOI: 10.21162/pakjas/16.1502
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Soil and Water Conservation Terrace Structures for Improvement of Crops and Soil Productivity in Rainfed Terraced System

Abstract: FPWOS). Results of this experiment revealed that TS has increased the wheat grain yield significantly (20%) through conservation of soil moisture contents (16 %) and soil fertility level. TS had decreased the gullies/rills formation through the efficient removal of excess rainwater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 17 publications
2
26
0
1
Order By: Relevance
“…Relationship between fertilizer, water-retaining agent, and nutrient runoff in substrate material: F1-F5 and W1-W5 represent 5 different gradients of fertilizer and content of water-retaining agent, respectively; uncertainty is represented as the standard deviation of the mean of 3 replicated plots. a) b) [27]. In contrast, the water-retaining agent treatments decreased the potassium concentration in the runoff samples.…”
Section: Resultsmentioning
confidence: 95%
“…Relationship between fertilizer, water-retaining agent, and nutrient runoff in substrate material: F1-F5 and W1-W5 represent 5 different gradients of fertilizer and content of water-retaining agent, respectively; uncertainty is represented as the standard deviation of the mean of 3 replicated plots. a) b) [27]. In contrast, the water-retaining agent treatments decreased the potassium concentration in the runoff samples.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, several studies indicated how terraces, especially those made with stones, favor drainage, water conservation (Chow et al, 1999), and groundwater recharge (Liu et al, 2004). Schiettecatte et al (2005) and Rashid et al (2016) considered terraces very effective water harvesting techniques.…”
Section: Provisioning Ecosystem Servicesmentioning
confidence: 99%
“…Terraces can reduce water erosion significantly, provided they have been properly planned, constructed, and maintained; otherwise, they can cause land degradation and increase erosion (Dorren & Rey, 2004;Romero Díaz et al, 2007). The important role of terraces in water regulation has been shown on numerous occasions, from the ancient Mayan terraces (Beach et al, 2002) to those of Pakistan (Rashid et al, 2016), China (Liu et al, 2004), andSpain (Reynes Trias, 2006). One consequence of the regulation of runoff, increased infiltration, and enhanced recharge of aquifers (Liu et al, 2004) is the reduction of floods (Wei et al, 2016).…”
Section: Regulating Ecosystem Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sloping terraces in Sichuan Province of southern China reduced runoff and sediment yield by 41% and 80.1%, respectively (Zhang et al, 2008). In general, terracing was considered a successful approach to the control of water erosion in those regions with steep slopes and erodible soils (Rashid et al, 2016;Kovar et al, 2016). However, terraced landscapes subject to abandonment can progressively increase gully erosion and cause terrace failure (Tarolli et al, 2014).…”
Section: Introductionmentioning
confidence: 99%